PENGETAHUAN IBU HAMIL TENTANG KEBIASAAN KONSUMSI JUNK FOOD DI KLINIK BROMO MEDAN TAHUN 2016 - Lili Nurmaliza (Jurnal Riset Hesti Medan, 2016)
Fulfillment of nutrition for pregnant women is indeed not yet fully realized by the people of Indonesia. It should be noted that the proliferation of junk food tends to result in a lack of nutritional intake which can cause congenital defects in the central nervous system and fetal brain. The aim of the study was to describe the knowledge of pregnant women about the consumption habits of junk food at the Bromo Clinic in Medan. Research is descriptive with a population that is all pregnant women who visit the Bromo clinic with a sample of 14 respondents conducted by purposive sampling. Data analysis was carried out descriptively.The results of the study showed that the majority of pregnant women's knowledge was sufficient (71.42%) and knowledgeable (14.29%). Based on the age of the majority of knowledgeable enough (64.28%), the majority of education is sufficiently knowledgeable (64,285), the work of the majority of sufficient knowledge (57,14%) and the majority of information sources are sufficiently knowledgeable (42,86%). The conclusion is that the knowledge of pregnant women about the consumption habits of junk food at the Bromo Clinic is knowledgeable. It is recommended for pregnant women not to consume junk food.